The Ethics of Humanitarian Innovation: Mapping Values Statements and Engaging with Value-Sensitive Design - Brahimi, Lilia; Krishnaraj, Gautham; Pringle, John; Schwartz, Lisa; O’Mathúna, Dónal; Hunt, Matthew (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
The humanitarian sector continually faces organizational and operational challenges to respond to the needs of populations affected by war, disaster, displacement, and health emergencies. With the goal of improving the effectiveness and efficiency of response efforts, humanitarian innovation initiatives seek to develop, test, and scale a variety of novel and adapted practices, products, and systems. The innovation process raises important ethical considerations, such as appropriately engaging crisis-affected populations in defining problems and identifying potential solutions, mitigating risks, ensuring accountability, sharing benefits fairly, and managing expectations. This paper aims to contribute to knowledge and practice regarding humanitarian innovation ethics and presents two components related to a value-sensitive approach to humanitarian innovation. First is a mapping of how ethical concepts are mobilized in values statements that have been produced by a diverse set of organizations involved in humanitarian innovation. Analyzing these documents, we identified six primary values (do-no-harm, autonomy, justice, accountability, sustainability, and inclusivity) around which we grouped 12 secondary values and 10 associated concepts. Second are two proposed activities that teams engaged in humanitarian innovation can employ to foreground values as they develop and refine their project’s design, and to anticipate and plan for challenges in enacting these values across the phases of their project. A deliberate and tangible approach to engaging with values within humanitarian innovation design can help to ground humanitarian innovation in ethical commitments by increasing shared understanding amongst team members, promoting attentiveness to values across the stages of innovation, and fostering capacities to anticipate and respond to ethically challenging situations.